Combinatorial locational analysis of public services in metropolitan areas. Case study in the city of Volos, Greece. - Fotini Athanasiou; Yorgos Photis (European Regional Science Association (ERSA), 2004)
Social prosperity largely depends on spatial structure, a relation which becomes stronger in urban areas where the quality of life is menaced by several factors. Traffic, over-building, lack of open space and deficient location of services come to the fore. The latter reflects access inequality and is one of the main reasons for everyday movement difficulties of citizens. Particularly, public services, as part of the public sector, are considered to be driven by the principle of social well-fare. Therefore the study of their location gives rise to the question: how can access of city blocks to public services be evaluated and how can the results of this evaluation be combined with the monetary values assigned by the state? In this respect, the main aim of this paper is the determination of a synthetic methodological framework for the locational analysis and evaluation of public services in urban areas. The proposed approach is based on spatial analysis methods and techniques as well as on the analytical capabilities of GIS and finally leads to the definition of the locational value for each city block. The public services are classified according to served population age groups and to their yearly utilization levels. The minimum and average Manhattan distances to the services of each classification group are calculated along with the percentages of services that are closer than a critical radius to each city block. At the final step, city blocks are classified through the use of cluster analysis to the calculated distances and percentages and then ranked according to their overall accessibility to public services. Their score is utilized in the definition of their locational value and in the formulation of a combinatorial index which compares locational and land values throughout the study area. The methodological framework is applied in the city of Volos where according to the results of the analytical process the majority of city blocks (60,7%) indicates a comparatively lower locational than monetary land value.
Keywords: 330